DIVERSITY OF FISH LARVAE AROUND THE ESTUARY OF THE BANYUASIN RIVER, SOUTH SUMATERA PROVINCE - Ridho, Moh. Rasyid; Patriono, Enggar; Sarno, Sarno; Wirda, Sahira (BIOVALENTIA: Biological Research Journal, 2020)
The initial phase of the fish life cycle is a critical phase associated with high mortality due to sensitivity to predators, food availability, and also environmental changes that occur in nature. Disruption of the initial stages of fish life has a negative impact on fish populations. Until now there has been no information about fish larvae around the Banyuasin River Estuary. Therefore, research is needed on the diversity of fish larvae around the Banyuasin River Estuary, South Sumatra Province. This research were used purposive sampling method, sampling technique in the form of Cruise Track Design with continuous parallel survey trajectory. Based on the results of the study found as many as 10 families consisting of 1483 individuals of fish larvae in March and 1013 individuals of fish larvae in May consisting of Engraulidae 1,601 individuals of fish larvae, Mungiloidei as many as 109 individuals, Leiognathidae 50 individuals, Chanidae 453 individuals, Scatophagidae 20 individuals , Belonidae 39 individuals, Gobioididae 5 individuals, Chandidae 183 individuals, Syngnatihidae 6 individuals, and Gobiidae 30 individuals fish larvae. The index value of fish larvae diversity is classified as medium category (March 1.02 and May 1.12), Morisita index shows the distribution pattern of fish larvae classified as a group (March 0-14.17 and May 2.43-10.40 ), and the evenness index value is in the medium category (March 0.437 and May 0.521).